Associations between diet quality, food insecurity, physical activity, social connectedness and depressive symptomology in Australian university students: a cross-sectional study - O’Neill, Simone; Minehan, Michelle; Knight-Agarwal, Catherine R.; Lewis, Vivienne; Pyne, David B. (Frontiers in Nutrition, 2025)
ObjectiveRising prevalence of depression demands focus on modifiable factors to improve mental health outcomes. An inverse relationship has been identified between diet quality and depressive symptomology. This cross-sectional study aimed to examine how food insecurity, physical activity and social connectedness contribute to the relationship between diet quality and depressive symptomology.MethodsData was collected from adult university students (n = 145, age = 26.9 ± 9.9 years) between July and October 2024 using an electronic survey. Included scales were the Diet Screening Tool, the US Adult Food Security Module, the International Physical Activity Questionnaire, the Social Connectedness Scale and the Depression, Anxiety and Stress Scale—21. Pearson’s correlation analyses and linear regression were performed exploring the associations for variables of interest.ResultsThe university student cohort was characterized by mild–severe depression (70%) and severe food insecurity (25%). The results showed increased food insecurity and physical activity (Metabolic Equivalent Task minutes/week) account for 11% and 9% of the variation seen in DASS-21 depression scores, respectively. Diet quality and social connections were not found to have a significant association with depressive symptomology.ConclusionIt appears that food insecurity could be a contributing factor impacting depressive symptomology, and if addressed effectively could improve mood disorder treatments. The relationship between physical activity and depression is counterintuitive and warrants further investigation. Implementing evidence-based holistic interventions that address food insecurity should be considered to support the mental health of university students.